'I didn't realise the variety of people that are climbers': a sociological exploration of young women's propensities to engage in indoor rock climbing. Issue 4 (4th July 2022) - Hewitt, Jack Ryan; McEvilly, Nollaig
ABSTRACT: This paper focuses on the increasingly popular leisure pursuit of indoor rock climbing amongst young women in the UK. Adopting a Bourdieusian perspective, we draw on the concepts of field, habitus and capital to explore the factors associated with young women's propensities to start, and continue, engaging in this activity. Data were generated through semi-structured interviews with 12 women (aged 18–25), who had been regularly engaging in indoor climbing for at least six months. Thematic analysis of the transcripts led to the construction of three themes: preconceptions of a masculine field; habitual feelings of intimidation and inferiority; and deploying and accruing 'climbing capital'. The findings indicate that climbing's deep-rooted classification as a 'man's sport' initially facilitated feelings of intimidation and inferiority amongst the women, inhibiting their propensity to participate. However, having been introduced to climbing (often by men, such as their boyfriends or brothers), the women found that the social aspects of the activity, along with the sense of achievement they felt when participating, meant they re-evaluated their preconceptions of the field. Their access to various forms of capital facilitated their continued engagement in the field.